(3CfjS GdabgGAs - (3Gdbhfhj, bGSe Hf YHO Gddg, J (B978 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj ced BdGDg hHYO adeG CUHJ GUWdGMGJ GdabgGA aj GdcJH aGdJCLJ ef aJQI GdNhGWQ Edi MUhf GdYdeGA eJhSeG HCfjS GdabgGAs
(3BNQgG (B:s
(3aGdabjg gh GdYGde jYde GdTQjYI GdTQjaI GdWQjbI GdXGgQI aj GdOjf cPG aj GdeZQH haj GdUMGM hGdTQjYI eG TQYg Gddg SHMGfg JHGQc hJYGdi HYHGOI ef GdOjf Cj CWgQI hHjfg GdeTQhYGJ CQHYI CjVG GdcJGH hGdSfI hELeGY GdCeIs
(3fSNI efbhdI Yf fSNI efbhdI Yf fSNI GdeUefa bGSe Gdbhfhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2 / 644s
(3EjVGM Gdecfhf (B1 / 149s
(3gOjI GdYGQajf (B1 / 832s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs